Inclusive-jet cross sections in NC DIS at HERA and a comparison of the k(T), anti-k(T) and SIScone jet algorithms - Abramowicz, H.; Abt, I.; Adamczyk, L.; Adamus, M.; Aggarwal, R.; Antonelli, S.; Antonioli, P.; Antonov, A.; Arneodo, M.; Aushev, V.; Aushev, Y.; Bachynska, O.; et al. (Elsevier, 2010)
For the first time, differential inclusive-jet cross sections have been measured in neutral current deep inelastic ep scattering using the anti-k(T) and SIScone algorithms. The measurements were made for boson virtualities Q(2) > 125 GeV2 with the ZEUS detector at HERA using an integrated luminosity of 82 pb(-1) and the jets were identified in the Breit frame. The performance and suitability of the jet algorithms for their use in hadron-like reactions were investigated by comparing the measurements to those performed with the k(T) algorithm. Next-to-leading-order QCD calculations give a good description of the measurements. Measurements of the ratios of cross sections using different jet algorithms are also presented; the measured ratios are well described by calculations including up to O(alpha(3)(s)) terms. Values of alpha(s)(M-z) were extracted from the data; the results are compatible with and have similar precision to the value extracted from the kT analysis. (C) 2010 Elsevier B.V. All rights reserved.